Sensitivity enhancement of a Cu (II) metal organic framework-acetylene black-based electrochemical sensor for ultrasensitive detection of imatinib in clinical samples - Xu, Xuanming; Li, Shun; Luan, Xingwei; Xuan, Chao; Zhao, Peng; Zhou, Tingting; Tian, Qingwu; Pan, Deng (Frontiers in Chemistry, 2023)
Imatinib (IMB), an anticancer drug, is extensively used for chemotherapy to improve the quality of life of cancer patients. The aim of therapeutic drug monitoring (TDM) is to guide and evaluate the medicinal therapy, and then optimize the clinical effect of individual dosing regimens. In this work, a highly sensitive and selective electrochemical sensor based on glassy carbon electrode (GCE) modified with acetylene black (AB) and a Cu (II) metal organic framework (CuMOF) was developed to measure the concentration of IMB. CuMOF with preferable adsorbability and AB with excellent electrical conductivity functioned cooperatively to enhance the analytical determination of IMB. The modified electrodes were characterized using X-rays diffraction (XRD), X-ray photoelectron spectroscopy (XPS), fourier transform infrared (FT-IR), ultraviolet and visible spectrophotometry (UV-vis), electrochemical impedance spectroscopy (EIS), scanning electron microscopy (SEM), energy dispersive X‐ray spectroscopy (EDS), brunauer‒emmett‒teller (BET) and barrett‒joyner‒halenda (BJH) techniques. Analytical parameters such as the ratio of CuMOF to AB, dropping volumes, pH, scanning rate and accumulation time were investigated through cyclic voltammetry (CV). Under optimal conditions, the sensor exhibited an excellent electrocatalytic response for IMB detection, and two linear detection ranges were obatined of 2.5 nM-1.0 μM and 1.0-6.0 μM with a detection limit (DL) of 1.7 nM (S/N=3). Finally, the good electroanalytical ability of CuMOF-AB/GCE sensor facilitated the successful determination of IMB in human serum samples. Due to its acceptable selectivity, repeatability and long-term stability, this sensor shows promising application prospects in the detection of IMB in clinical samples.